THE CURRENT STATE OF DATA TRANSMISSION CHANNELS FROM PUSHCHINO TO MOSCOW AND PERSPECTIVES - Dumsky, D. V.; Isaev, E. A.; Samodurov, V. A.; Shatskaya, M. V. (Одеські астрономічні публікації, 2016)
Since the work of a unique space radio telescope in the international VLBI project ”Radioastron” extended to 2017 the transmission and storage of large volumes of scientific and telemetry data obtained during the experiments is still remains actual. This project is carried out by theAstroSpaceCenter of Lebedev Physical Institute inMoscow,Russia. It requires us to maintain in operating state the high-speed link to merge into a single LAN buffer data center in Puschino and scientific information center inMoscow. Still relevant the chanal equipment monitoring system, and storage systems, as well as the timely replacement of hardware and software upgrades, backups, and documentation of the network infrastructure.